Intellectual Capital and Uncertainty of Knowledge: Control by Design of the Management System - Herremans, Irene M. (Journal of business ethics, 2011)
This research, couched in the resource-based view of the firm, investigates the potential for reducing an organization’s decision uncertainty within its intellectual capital (IC) operating environment. Using structural equation modeling, we empirically test if organizational design can reduce the perceived uncertainty related to an IC context, which we refer to as knowledge uncertainty. We found evidence that decentralization and technology infrastructure support a results-based IC management control system which in turn is associated with reduced internal decision uncertainty. Finally, our statistics support a good overall fit for our model. Our findings suggest that if managers structure their organizational control systems appropriately for developing IC capabilities, these systems can lead to reduced internal uncertainty regarding human, structural, and relational capital.